Seed dispersal by Neotropical bats in human-disturbed landscapes - Regolin, Andre Luis [UNESP] (2020)
In human-modified landscapes, where large bird and mammal species are often functionally extinct, bats are the main seed dispersers. However, the role of seed dispersal by bats for the maintenance of habitat dynamics in fragmented landscapes is still not understood, with information lacking on landscape-level effects of plant-bat interactions. We present some key topics related to spatial ecology of bats and discuss the potential influence of habitat fragmentation on several aspects of seed dispersal by Neotropical bats. We suggest that future studies need to evaluate bat-plant networks along habitat-loss and fragmentation gradients at the landscape level, including changes in land-cover types and habitat structural complexity, going beyond patch-based analysis. By advancing on the comprehension of ecosystem functioning in fragmented landscapes, we will better understand the bat-modulated seed-dispersal process, supporting regeneration and restoration programs that benefit from bat-based functions.